2005
DOI: 10.1007/s00421-005-1352-1
|View full text |Cite
|
Sign up to set email alerts
|

The reproducibility of an endurance performance test in adolescent cyclists

Abstract: The purpose of the study was to measure the reproducibility of a performance test in well-trained adolescent cyclists. Eight male and one female cyclist [mean age 15.7 (0.7) y] participated in the study. Lactate threshold (LT) and peak VO2 were assessed. The performance test was repeated on three separate days and consisted of 30 min of steady state (SS) cycling at 80% of individual LT. Immediately after the SS cycling a time trial (TT) started with the cyclists having to complete a fixed amount of work as fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Young athletes tend to have higher levels of aerobic power per unit body mass than the general population children and youth non-athletes (Malina, Bouchard & Bar-Or, 2004). This trend finds echo in previous researches (Eisenman, Pivarnik&Malina, 2001;Chamari et al, 2004;Montfort-Steiger, Williams & Armstrong, 2005;Metaxas, Koutlianos, Kouidi&Deliggianis, 2005;Castagna, Impellizzeri, Rampinini, D´Ottavio&Manzi, 2008). Our results strengthen the framework of evidence and show youth soccer players as athletes who demonstrate values of relative peak VO2 similar to those find for their peers from other sports.…”
Section: Discussionmentioning
confidence: 57%
“…Young athletes tend to have higher levels of aerobic power per unit body mass than the general population children and youth non-athletes (Malina, Bouchard & Bar-Or, 2004). This trend finds echo in previous researches (Eisenman, Pivarnik&Malina, 2001;Chamari et al, 2004;Montfort-Steiger, Williams & Armstrong, 2005;Metaxas, Koutlianos, Kouidi&Deliggianis, 2005;Castagna, Impellizzeri, Rampinini, D´Ottavio&Manzi, 2008). Our results strengthen the framework of evidence and show youth soccer players as athletes who demonstrate values of relative peak VO2 similar to those find for their peers from other sports.…”
Section: Discussionmentioning
confidence: 57%
“…For these reasons, and added to the fact that participants were previously unfamiliar with the type of test, it would seem prudent to include a trial to familiarise (habituate) such participants with a protocol. Other recent studies have also concluded this, such as Montfort-Steiger et al (2005) who suggest that for the evaluation of the effectiveness of a nutritional intervention in less experienced participants, a habituation trial is essential to optimise between-test variability, as this impacts on sample size estimates. Despite this, in trained and habituated cyclists, it is suggested that a familiarisation trial may not be needed.…”
Section: Discussionmentioning
confidence: 92%
“…Despite the lack of extensive experience of cycling as an exercise mode and/or the laboratory testing environment, reliability of 3.4% (mean CV for the group using typical error) and 6.3% (CV of individual values) in recreationally active participants compares reasonably well with other studies evaluating similar types of test in trained cyclists. Literature examples include 3-4% in trained cyclists using a cycle ergometer (Jeukendrup et al 1996), 3.7% in adolescent cyclists (Montfort-Steiger et al 2005), and 3.8-4.5% in trained cyclists in a glycogendepleted state (Currell et al 2006). The pre-load exercise intensity used in the present study (65% of peak VO 2 ) is Jeukendrup et al 1996).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the order of the trials was counterbalanced, the inclusion of a habituation session has been suggested to reduce the coefficient of variation in adolescents completing a cycling time trial (Montfort-Steiger et al 2005). …”
Section: Performancementioning
confidence: 99%